The Doctor’s Doctor Is the Patient’s Doctor: A Pilot Quality Improvement Study on Patient-Pathologist Consultations at a Single Institution - Katherine Drews-Elger; Merce Jorda; Melissa Stedman; Sophie Egea; Elena F. Brachtel; Susan B. Kesmodel; Jose M. Net; Monica M. Yepes; Carmen Gomez-Fernandez (Archives of Pathology & Laboratory Medicine, 2026)
Context.— Pathologists have traditionally worked behind the scenes, providing diagnostic information to clinicians. The 21st Century Cures Act grants patients immediate access to pathology reports, creating opportunities and challenges for patient-pathologist communication. Objective.— To evaluate the feasibility, acceptance, educational value, and perceived impact of telehealth-based, language-concordant patient-pathologist consultations for patients with breast biopsies across the full diagnostic spectrum. Design.— Prospective, single-institution quality improvement pilot study at a tertiary care cancer center involving a breast pathologist, 2 breast radiologists, 1 breast surgeon, and 1 pathology resident. Patients undergoing a breast biopsy were offered an optional 30-minute telehealth consultation with a breast pathologist and a pathology resident to review their findings and biopsy slides in their preferred language (English or Spanish). Postconsultation surveys assessed patient perceptions. Encounters were documented in pathology reports and shared with referring physicians. Results.— Forty-three patients were offered the consultation and more than half elected to participate. Consultations spanned benign, premalignant, and malignant diagnoses and were integrated without disrupting existing care pathways. Surveys indicated high patient satisfaction, improved understanding of pathology results, and reduced anxiety. Patients valued slide review and direct discussion with the diagnosing pathologist. Telehealth delivery and language concordance were well received. Resident participation was acceptable and supported educational goals. Conclusions.— Telehealth-based, language-concordant patient-pathologist consultations in breast pathology are feasible, well accepted, and enhance patient understanding. This model integrates into routine workflows, supports trainee education, and warrants broader evaluation as a scalable, patient-centered approach to diagnostic care.